2017
DOI: 10.17116/jnevro201711771112-119
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic application of zinc and vitamin C to support memory, attention and the reduction of the risk of the neurological diseases

Abstract: Zinc and vitamin C supplementation of the body is important for CNS functioning. Zinc ions are involved in the neurotransmission (signal transmission from acetylcholine, catecholamine, serotonin, prostaglandin receptors) and in ubiquitin-related protein degradation. Zinc deficits are associated with Alzheimer's disease and depression. Zinc supplementation (10-30 mg daily) improves neurologic recovery rate in patients with stroke and brain injury, has a positive impact on memory and reduces hyperactivity in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Interestingly, we observed that zinc ion binding was common in female and male samples. Zinc ion is an endogenous neuromodulator widely found in the central nervous system (54) 54 , and its de ciency increases the risk of neurological disease(55) 55 . We may infer that zinc-related pathways are potentially related to personal traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we observed that zinc ion binding was common in female and male samples. Zinc ion is an endogenous neuromodulator widely found in the central nervous system (54) 54 , and its de ciency increases the risk of neurological disease(55) 55 . We may infer that zinc-related pathways are potentially related to personal traits.…”
Section: Discussionmentioning
confidence: 99%
“…widely found in the central nervous system (54) 54 , and its de ciency increases the risk of neurological disease(55) 55 . We may infer that zinc-related pathways are potentially related to personal traits.…”
Section: Discussionmentioning
confidence: 99%
“…Algumas pesquisas revelam o uso de vitaminas e antioxidantes nas condições neuropsiquiátricas tendo resultados benéficos. A vitamina C, um sinergista de zinco, mantém os recursos antioxidantes do cérebro, atividade sináptica e desintoxicação em humanos (Gromova et al, 2017). Além das vitaminas, outros antioxidantes não enzimáticos são também encontrados nos alimentos in natura, como os polifenóis.…”
Section: Introductionunclassified